The effect of using language patterns on teaching Basic Arabic subject to the 1st year students of the Department of Islamic Studies at South Eastern University of Sri Lanka - Sithy Shathifa Mohammed Cassim; Muhammadu Sainulabdeen Zunoomy (Indonesian Journal of Arabic Studies, 2022)
This research aims to find the effect of using language patterns in teaching Arabic grammar to the first year undergraduates of the department of Islamic studies at South Eastern University of Sri Lanka. They learn Arabic language as auxiliary subject â€œBasic Arabicâ€ in two semesters of first year. Because, they have basic knowledge about it from reciting Holy Quran and they couldnâ€™t pronounce the Arabic words without shakl. According to this, they need to various methods to learn Arabic. Therefore, this research uses language pattern to teach Arabic to 50 students form the academic year 2018/19. They were divided into two groups of 25 members in accordance with their language ability to compare the impact the teaching of language patterns with theory based teaching through quantitative and qualitative approaches. The primary data were collected from questionnaire, observation which occurred during teaching process and interview with lecturers of the department. It finds that various methods are followed in teaching Arabic grammar, either theoretically or in practice. The students have understood Arabic grammar clearly when using the language patterns after explaining the grammar theoretically. As well as teaching the grammar based on theories leads to boring, while the students participated actively through the language patterns, they could express the sentences mentioned in the examples. Because they could understand the language replacement and its utilization in language learning. So, this study declares that the teaching grammar by using language patterns is an effective way than teaching based on theories.